A construction of Shatz strata in the polystable $ G_2 $-bundles moduli space using Hecke curves - Álvaro Antón-Sancho (Electronic Research Archive)
Let $ X $ be a compact Riemann surface of genus $ g≥ 2 $ and $ M(G_2) $ be the moduli space of polystable principal $ G_2 $-bundles over $ X $. The Harder-Narasimhan types of the bundles induced a stratification of the moduli space $ M(G_2) $ called Shatz stratification. In this paper, a description of the Shatz strata of the unstable locus of $ M(G_2) $ corresponding to certain family of Harder-Narasimhan types (specifically, those of the form $ (λ, μ, 0, -μ, -λ) $ with $ μ < λ≤ 0 $) was given. For this purpose, a family of vector bundles was constructed in which a 3-form and a 2-form were defined so that it was proved that they were strictly polystable principal $ G_2 $-bundles. From this, it was proved that, when the genus of $ X $ was $ g≥ 12 $, these Shatz strata were the disjoint union of a family of $ G_2 $-Hecke curves in $ M(G_2) $ that will be constructed along the paper. Therefore, the presented results provided an advance in the knowledge of the geometry of $ M(G_2) $ through the study of its Shatz strata and presented a methodological innovation, by using Hecke curves for this study.